Improved Performance of Electroplated CZTS Thin‐Film Solar Cells with Bifacial Configuration. Issue 16 (11th July 2016) - Ge, Jie; Yu, Yue; Ke, Weijun; Li, Jian; Tan, Xinxuan; Wang, Zhiwei; Chu, Junhao; Yan, Yanfa
Abstract: Annealing in S vapor greatly improves the performance of electroplated Cu2 ZnSnS4 (CZTS) solar cells based on the bifacial configuration of Al‐doped ZnO (AZO, front contact)/ZnO/CdS/CZTS/indium tin oxide (ITO, back contact), as compared to H2 S annealing in our previous works. S‐vapor annealing does not cause severe damage to the conductivity of the ITO back contact. The highest device efficiency of 5.8 % was reached under 1 sun illumination from the AZO side. The well‐preformed devices based on the ITO back contact demonstrate smaller series resistances and better fill factors, as compared to our substrate‐type devices using Mo back contacts. An interfacial reaction at the ITO back contact has been revealed in experiments, which contributes to the formation of SnO2 ‐enriched interfacial layer and diffusion of In from ITO into CZTS through the Sn sites. Incorporation of In does not significantly change the optical and structural properties or the grain size of CZTS absorbers. Abstract : Bifacial CZTS : Solar cell device performance is greatly improved by annealing Cu2 ZnSnS4 (CZTS) films in S vapor. The highest efficiency of 5.8 % is achieved under 1 sun illumination from the Al‐doped ZnO (AZO) front contact. An interfacial reaction between CZTS and indium tin oxide (ITO) back contact is presented, which contributes to the segregation of a SnO2 ‐enriched interfacial layer and diffusion of In from ITO into CZTS through Sn sites.